PRIMARY PREVENTION OF DIABETES MELLITUS: CORRECTION OF EARLY DISORDERS OF GLUCOSE METABOLISM IN CARDIOLOGY PRACTICE - M. N. Mamedov; E. A. Poddubskaya; M. N. Kovrigina; Z. O. Ugurchieva; R. T. Digigova (Столичная издательская компания, 2015)
Early glucose metabolism disorders (GMD) are of interest in development of effective approaches to prevention of type 2 diabetes mellitus (DM). Data of international clinical trials shows that early GMD are an independent risk factor for cardiovascular disease. The possibilities of GMD prevention and early treatment are discussed. Antihyperglycemic medications classification, their mode of action and efficacy are presented from evidence-based medicine point of view. This data confirms that successful DM primary prevention at early stage of GMD reduces the risk of cardiovascular complications.